2005
DOI: 10.1080/0887044042000334733
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the severity and duration of physical disability and body esteem

Abstract: The current study investigated the association between the severity and duration of physical disability and body esteem. A total of 748 participants (367 males, 381 females) who had a physical disability and 448 participants (171 males, 277 females) who were able-bodied participated in the study. The results demonstrated that people with more severe physical disability experienced lower levels of body esteem than people with milder physical disabilities and able-bodied people. The duration of physical disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
2
30
0
2
Order By: Relevance
“…En las personas con una diversidad funcional congénita, la primera fase no existe (Miangolarra y Álvarez, 2003). A lo largo del tiempo, se ha intentado diferenciar el impacto en la autoestima que puede provocar una diversidad funcional congénita y una diversidad funcional adquirida con posterioridad (Antle, 2004;Bishop, 2001;Grzesiak y Hicok, 1994;Taleporos y McCabe, 2005).…”
Section: Antecedentesunclassified
“…En las personas con una diversidad funcional congénita, la primera fase no existe (Miangolarra y Álvarez, 2003). A lo largo del tiempo, se ha intentado diferenciar el impacto en la autoestima que puede provocar una diversidad funcional congénita y una diversidad funcional adquirida con posterioridad (Antle, 2004;Bishop, 2001;Grzesiak y Hicok, 1994;Taleporos y McCabe, 2005).…”
Section: Antecedentesunclassified
“…Los resultados hallados en este estudio no son extrapolables a todas las personas con discapacidad física, dado que el grupo de participantes forma parte de una entidad sin ánimo de lucro que ofrece la inclusión social y laboral, y por ello el soporte social y la posibilidad de referenciarse a sí mismos con personas que tienen la misma condición hace que la aceptación a la discapacidad y la confianza en sí mismos mejoren significativamente y, por ende, aumente la valoración de su imagen corporal (Cash et al, 2004). Así mismo, la adecuada valoración de la imagen corporal que reportaron las personas del estudio se relaciona con la severidad de la discapacidad, el grado de la limitación y la dependencia de cuidadores para las actividades cotidianas, lo cual además facilita su participación en contextos laborales y sociales (Taleporos & McCabe, 2005).…”
Section: Calidad De Vidaunclassified
“…Two of the participants suggested that negative body esteem in people with Cerebral Palsy is linked to privatizations of the socio-sexual implications of physical impairment (Taleporos & McCabe, 2005). For instance, Alex indicated that negative body esteem influenced the way he privatized interactional sexual relationships.…”
Section: Negative Body Esteemmentioning
confidence: 99%